BS 8468-3.1. Respiratory protective devices for use against chemical, biological, radiological and nuclear (CBRN) agents. Part 3.1. Self-contained open-circuit compressed air breathing apparatus incorporating a hood for escape. Specification (3rd December 2019) - British Standards Institution
No abstract available